Virtual Reality and Light Field Immersive Video Technologies for Real-World Applications. - Lafruit, Gauthier (Institution of Engineering & Technology, 2022)
Inspired by MPEG-I and JPEG-PLENO standardization activities, this book is for readers who want to understand 3D representations and multi-camera video processing for novel immersive media applications. The authors address new challenges that arise beyond compression-only, such as depth acquisition and 3D rendering.
Keywords: Virtual reality.; elektronické knihy; electronic books